Problematika Implementasi Undang-Undang Nomor 18 Tahun 2019 tentang Pesantren pada Pondok Pesantren Bahrul Ulum Induk Tambakberas Jombang - Ilham Ula Aghna; Anis Humaidi (Lembaga Yasin AlSys, 2026)
This study was motivated by the gap between the normative provisions of Law Number 18 of 2019 on Pesantren and the realities of its implementation in pesantren settings, particularly in the area of educational governance. The study aimed to analyze the problems surrounding the implementation of Law Number 18 of 2019 on Pesantren at Pondok Pesantren Bahrul Ulum Induk Tambakberas Jombang. A qualitative approach with a case study design was employed, with research subjects including the pesantren caregivers, education managers, teaching staff, and administrative operators. Data were collected through in-depth interviews, observation, and document analysis, then analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The findings show that the implementation of the Pesantren Law has not yet been optimal in the areas of curriculum development, teacher qualification, quality assurance and accreditation, and EMIS data governance. The main constraints do not lie in the substance of pesantren education, but rather in limited administrative, managerial, and technical capacity, as well as differences in paradigm between state regulations and pesantren traditions. The study concludes that the implementation of the Pesantren Law requires an adaptive and contextual approach capable of integrating the strengths of pesantren tradition with the demands of national education governance in order to support the improvement of the quality of Islamic education in pesantren.